Functional response of plant assemblages to management practices in road–field boundaries. Issue 1 (19th November 2017) - Chaudron, Clémence; Perronne, Rémi; Di Pietro, Francesca
Abstract: Questions: Management practices implemented on road verges are partly established to preserve biodiversity in agricultural landscapes. Their evaluation was primarily based on the analysis of the taxonomic structure and composition of communities. What is the relationship between management practices and the functional characteristics of road–field plants within elements? Location: West‐central France. Methods: We sampled the berm, the embankment and the field margin of 40 road–field boundaries located in west‐central France, an area where delayed mowing of some berms has been practised since 2009 for biodiversity reasons. We characterized management practices implemented on the different elements, i.e., the frequency and timing of mowing (early summer or late summer), the frequency of herbicide treatment in field margins and the N input rate. We retrieved from databases seven functional traits and types known to be influenced by management practices. To identify relationships between traits or types and environmental variables we first performed partial RLQ analyses to remove any potential confounding effect of the landscape context studied. We then computed fourth‐corner statistics to quantify relationships between traits or types, environmental variables and partial RLQ axes. Results: Late mowing of the berm promoted nitrophilous species within berms and competitive rather than ruderal species within arable field margins. The frequency of herbicide treatment in field margins promoted broad‐leaf species within this element and, to a lesser extent, within embankments. Finally, the functional characteristics of communities of the three elements were not influenced by the level of N input in field margins. Conclusions: In our environmental context, managing road verges affected the functional structure of plant assemblages both within them and within their adjacent arable field margins. We suggest a single early mowing of berms as a valuable practice for both conservation purposes and weed risk control in adjacent field margins. Abstract : Management practices of road verges adjacent to arable fields are partly established for conservation purposes, usually relying on a taxonomic approach. Here, we performed partial RLQ analyses to quantify relationships between plant functional traits and management practices. We highlighted that late mowing of the berm favored nitrophilous species within berms and competitive rather than ruderal species within inner‐field margins.